2018
DOI: 10.3390/en11102737
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Airside Heat Transfer Augmentation with Vortex Generators on Heat Transfer Surface

Abstract: Heat exchanger performance can be improved via the introduction of vortex generators to the airside surface, based on the mechanism that the generated longitudinal vortices can disrupt the boundary layer growth, increase the turbulence intensity and produce secondary fluid flows over the heat transfer surfaces. The key objective of this paper is to provide a critical overview of published works relevant to such heat transfer surfaces. Different types of vortex generator are presented, and key experimental tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 111 publications
(220 reference statements)
0
15
0
Order By: Relevance
“…They found that using a double-triangle LVG increases the heat transfer coefficient more than that of a common LVG. LVG is produced by the VG winglet, which can reduce the thickness of the boundary layer, which impacts the heat transfer [8]. The longitudinal vortex (LV) produced by the winglet-type VG can enhance heat transfer better than the transverse vortex (TV) produced by the wing-type VG [9].…”
Section: Introductionmentioning
confidence: 99%
“…They found that using a double-triangle LVG increases the heat transfer coefficient more than that of a common LVG. LVG is produced by the VG winglet, which can reduce the thickness of the boundary layer, which impacts the heat transfer [8]. The longitudinal vortex (LV) produced by the winglet-type VG can enhance heat transfer better than the transverse vortex (TV) produced by the wing-type VG [9].…”
Section: Introductionmentioning
confidence: 99%
“…Plate-fin and tube heat exchangers are most widely used as evaporators and condensers in refrigeration systems (commercial refrigeration) and in other applications where heat transfer between liquid or evaporating/condensing fluid and gaseous working fluid is required. Proven technology, reliability, and relatively low cost of manufacture make platefin and tube heat exchangers very popular, not only as components of refrigeration units but also as gas coolers/heaters, recuperative heaters, dryers or heat pipe, thermosyphon radiators [1][2][3]. Nowadays, when detailed numerical simulations of fluid flow with heat transfer are within reach, many of the researchers carry out Computational Fluid Dynamics (CFD) studies to optimize the geometry of plate-fin and tube heat exchangers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of VGs: Transverse (TVG) and longitudinal vortex generators (LVG). TVG develop transverse vortices which are perpendicular to the flow direction, while LVG generate longitudinal vortices that last over long distances in the flow channel, resulting in a more efficient heat transfer enhancement [3,4]. The angle of attack, aspect ratio and LVG design have a significant effect on heat transfer enhancement, [5].…”
Section: Introductionmentioning
confidence: 99%